Novel Morphological Findings of Human Sperm Removal by Leukocytes in In Vivo and In Vitro Conditions: Preliminary Study. (26th June 2014) - Piasecka, Malgorzata; Fraczek, Monika; Gaczarzewicz, Dariusz; Gill, Kamil; Szumala‐Kakol, Anna; Kazienko, Anna; Laszczynska, Maria; Lenart, Stanislaw; Beutin, Lothar; Kurpisz, Maciej
<x xml:space="preserve">Abstract</x> Problem Biological significance of increased number of leukocytes in ejaculate remains a subject of controversy. The aim of this research was to describe the morphological characteristics of the sperm elimination by leukocytes in in vivo and in vitro conditions using natural stimulator of the immune system—uropathogenic Escherichia coli, O75:HNT, isolated from semen. Method of study The study was performed on ejaculated spermatozoa from normozoospermic men with leukocytospermia (n = 10, in vivo experiment) or without leukocytospermia (n = 15, in vitro experiment). Morphological observations were performed using light and scanning electron microscopy. Results Sperm removal by active leukocytes mediated by traditional phagocytosis and generation of extracellular traps were observed in in vivo and in vitro experiments. Conclusion Our morphological data suggest that human germ cells activate leukocytes triggering both traditional phagocytosis and a novel trapping mechanism, followed by extensive sperm elimination.